2022
DOI: 10.3390/nano12050806
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots’ Synthesis with a Strong Chemical Claw for Five Transition Metal Sensing in the Irving–Williams Series

Abstract: Carbon quantum dots (CQDs) are an excellent eco-friendly fluorescence material, ideal for various ecological testing systems. Herein, we establish uniform microwave synthesis of the group of carbon quantum dots with specific functionalization of ethylenediamine, diethylenetriamine, and three types of Trilon (A, B and C) with chelate claws -C-NH3. CQDs’ properties were studied and applied in order to sense metal cations in an aquatic environment. The results provide the determination of the fluorescence quench … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Furthermore, NACQD exhibited favorable fluorescence properties, as detailed in Figure S2 in the Supporting Information. Given that the amine and oxygen-containing groups on the surface of carbon quantum dots (CQDs) can chelate iron ions, we employed FTIR and XPS techniques to analyze the surface chemical structures of NACQD. , FTIR spectral analysis (Figure S3) demonstrated that the carbonyl (CO) stretches at 1631 and 1590 cm –1 , respectively, corresponding to the acetyl group and carboxyl group of aspirin. Compared to aspirin, the N–H bending vibration at 1482 cm –1 and a pronounced C–N stretch at 1345 cm –1 in the NACQD spectrum indicated successful surface amination.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, NACQD exhibited favorable fluorescence properties, as detailed in Figure S2 in the Supporting Information. Given that the amine and oxygen-containing groups on the surface of carbon quantum dots (CQDs) can chelate iron ions, we employed FTIR and XPS techniques to analyze the surface chemical structures of NACQD. , FTIR spectral analysis (Figure S3) demonstrated that the carbonyl (CO) stretches at 1631 and 1590 cm –1 , respectively, corresponding to the acetyl group and carboxyl group of aspirin. Compared to aspirin, the N–H bending vibration at 1482 cm –1 and a pronounced C–N stretch at 1345 cm –1 in the NACQD spectrum indicated successful surface amination.…”
Section: Resultsmentioning
confidence: 99%
“…Further, studies have shown that the fluorescence properties of CQDs and fluorimetry methodology were effectively applied for a carbon source with ethylenediamine and amino acids, ammonium salts and other amino derivatives [ 28 , 29 ]. Amino functional groups support the complexation chemical reaction between dots and pollutants.…”
Section: Introductionmentioning
confidence: 99%